2007
DOI: 10.1090/s0002-9947-07-04282-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-crossing partition lattices in finite real reflection groups

Abstract: Abstract. For a finite real reflection group W with Coxeter element γ we give a case-free proof that the closed interval, [I, γ], forms a lattice in the partial order on W induced by reflection length. Key to this is the construction of an isomorphic lattice of spherical simplicial complexes. We also prove that the greatest element in this latter lattice embeds in the type W simplicial generalised associahedron, and we use this fact to give a new proof that the geometric realisation of this associahedron is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
185
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(197 citation statements)
references
References 20 publications
2
185
0
2
Order By: Relevance
“…These theorems result from our formulae for the (combinatorial) decomposition numbers upon appropriate summations. Subsequently, it is shown that the corresponding formulae imply all known enumeration results on non-crossing partitions and generalised non-crossing partitions, plus several new ones; see Corollaries 12,14,[16][17][18][19] and the accompanying remarks. Section 9 presents the announced computational proof of the F = M (ex-)Conjecture for type D n , based on our formula in Corollary 19 for the rank-selected chain enumeration in the poset of generalised non-crossing partitions of type D n , while Section 10 addresses Conjecture 3.5.13 from [1], showing that it does not hold in general since it fails in type D n .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These theorems result from our formulae for the (combinatorial) decomposition numbers upon appropriate summations. Subsequently, it is shown that the corresponding formulae imply all known enumeration results on non-crossing partitions and generalised non-crossing partitions, plus several new ones; see Corollaries 12,14,[16][17][18][19] and the accompanying remarks. Section 9 presents the announced computational proof of the F = M (ex-)Conjecture for type D n , based on our formula in Corollary 19 for the rank-selected chain enumeration in the poset of generalised non-crossing partitions of type D n , while Section 10 addresses Conjecture 3.5.13 from [1], showing that it does not hold in general since it fails in type D n .…”
Section: Introductionmentioning
confidence: 93%
“…[2,3,4,5,8,9,14,15,16,17,20]). They reduce to the classical non-crossing partitions of Kreweras [30] for the irreducible reflection groups of type A n (i.e., the symmetric groups) and to Reiner's [32] type B n non-crossing partitions for the irreducible reflections groups of type B n .…”
Section: Introductionmentioning
confidence: 99%
“…Another connection between noncrossing partitions and clusters has arisen recently. Brady and Watt [9] construct a simplicial fan associated to c-noncrossing partitions (for bipartite c) and extend their construction to produce the c-cluster fan. Athanasiadis, Brady, McCammond and Watt [1] use the construction of [9] to give a bijection between clusters and noncrossing partitions.…”
Section: Introductionmentioning
confidence: 99%
“…Brady and Watt [9] construct a simplicial fan associated to c-noncrossing partitions (for bipartite c) and extend their construction to produce the c-cluster fan. Athanasiadis, Brady, McCammond and Watt [1] use the construction of [9] to give a bijection between clusters and noncrossing partitions. Their proof uses no type by type arguments and provides a different bijective proof that the k th entry of the h-vector of the c-cluster fan coincides with the number of c-noncrossing partitions of rank k. The bijection of [1] incorporates elements which are similar in appearance to the constructions of the present paper (see Remark 11.5), but many details of the relation between the two theories remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Section 2 includes background on simplicial complexes, (generalized) cluster complexes and a related partial order on a finite real reflection group. In particular, a new characterization (Theorem 2.3) of ∆ m (Φ), due to the second author [20,21], is reviewed, generalizing the one for ∆(Φ) given by T. Brady and C. Watt [9,Section 8]. The proof of Theorem 1.1, which relies on this characterization, is given in Section 3.…”
Section: Introductionmentioning
confidence: 99%